2013
DOI: 10.1016/j.chembiol.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Curli Assembly and Pellicle Biofilm Formation by Chemical and Protein Chaperones

Abstract: SUMMARY Enteric bacteria assemble functional amyloid fibers, curli, on their surfaces that share structural and biochemical properties with disease-associated amyloids. Here, we test rationally designed 2-pyridone compounds for their ability to alter amyloid formation of the major curli subunit CsgA. We identified several compounds that discourage CsgA amyloid formation and several compounds that accelerate CsgA amyloid formation. The ability of inhibitor compounds to stop growing CsgA fibers was compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 48 publications
1
85
0
Order By: Relevance
“…Images were captured on an Olympus SZX16 microscope with an Olympus DP72 camera. Pellicles were prepared by adding 2 l of the overnight culture into 2 ml of YESCA medium and grown statically at 26°C for 48 h (20). Pellicles were stained with 2 ml 0.1% (wt/vol) crystal violet for 5 min, followed by 3 washes with 2 ml H 2 O, and then were imaged on a Fluorchem 8900 (Alpha Innotech, San Leandro, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured on an Olympus SZX16 microscope with an Olympus DP72 camera. Pellicles were prepared by adding 2 l of the overnight culture into 2 ml of YESCA medium and grown statically at 26°C for 48 h (20). Pellicles were stained with 2 ml 0.1% (wt/vol) crystal violet for 5 min, followed by 3 washes with 2 ml H 2 O, and then were imaged on a Fluorchem 8900 (Alpha Innotech, San Leandro, CA).…”
Section: Methodsmentioning
confidence: 99%
“…prevents the curli-dependent pellicle biofilm formation by E. coli at the air-liquid interface of a static culture (40). Recently, cryo-EM data have shown that CsgE binds to the periplasmic domain of CsgG with 9:9 (CsgE:CsgG subunit) stoichiometry and forms a capping adaptor that closes off the periplasmic face of the CsgG secretion channel (37).…”
Section: Significancementioning
confidence: 99%
“…Fredrik Almqvist (Umea University, Umea, Sweden) discussed nonbiocidal approaches targeting pilus fibers and curli amyloids involved in biofilm formation. Dr. Almqvist described how the discovery and improvement of anti-␤-amyloid lead compounds not only could inhibit bacterial biofilm formation but also may inform studies on human amyloid-related diseases (29). Cagla Tukel (Temple University, Philadelphia, PA) showed surprising results suggesting that amyloidcontaining biofilms trigger autoimmunity.…”
Section: New Insights Into Antimicrobial Tolerance and Novel Targets mentioning
confidence: 99%